Jenis Pengembangan Keprofesian dan Konsepsi terhadap Lesson Study Learning Community pada Guru IPA SMP Kota Surakarta - Sugiharto, Bowo; Prayitno, Baskoro Adi; Widoretno, Sri; Sarwanto, Sarwanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Professional development of teachers is ideally continuous implemented and is known by Continuous Proffesional Development (CPD). CPD is a renewal conscious knowledge and improving the competence of teachers throughout his working life. This study is a descriptive study that aims to depict of the kinds of professional development and the conception of the Lesson Study Learning Community (LSLC) on junior high science teacher in Surakarta. The subjects were science teachers of junior high school of Surakarta both public and private schools with a sample of 10 teachers. This survey study conducted in June 2016 using an open questionnaire instrument. Analysis of data used qualitative data analysis type of Miles and Huberman model which included data reduction, data presentation, and drawing conclusions and verification. The results of this study concluded that the types of professional development carried out by the science teachers Surakarta includes activities Subject Teachers Council, education and training, workshops, and technical guidance. The study also revealed there has been no increase in professionalism is done by directly observing in the classroom is done in a sustainable manner. While Lesson Study is understood by science teachers with various understanding some of which has led to the understanding of LS as the collective activities of teachers. Learning community is understood as a group or study together.Keywords: teachers proffesional development, conception of lesson study learning community, science teacher